Students’ Learning Strategies in Dealing with Speaking Anxiety at Universitas Negeri Makassar - Ade Surya Anugrah; Syarifuddin Dollah; Sukardi Weda (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Speaking is one of the four fundamental skills in learning English language beside writing, reading, and listening. While it is condemned important, many students still struggle in mastering speaking skill. There are many reasons on why students might have trouble in speaking and one of them is excessive anxiety. With this situation, many students recommended to use learning strategies to help them in overcoming their speaking anxiety. This study provides us with knowledge about what learning strategies that students use to overcome speaking anxiety by implementing qualitative descriptive methods. The research subjects consist of ten (10) undergraduate students from English Education Program at Universitas Negeri Makassar. The study’s data collected with the help of non-participant observations and semi-structured interview sessions. After the data were collected and analyze, the researcher was able to identify fifteen (15) kinds of learning techniques that the students use to cope with their speaking anxiety. These fifteen (15) kinds of learning techniques are then categorized into three types of learning strategies, namely cognitive, meta-cognitive, and socio-affective learning strategies.